A state-of-the-art review of measurement and modelling of skid resistance: The perspective of developing nation - Kumar, Abhinav; Tang, Tianchi; Gupta, Ankit; Anupam, Kumar (Elsevier Ltd, 2023)
A critical review of lab and field measurement methodologies, harmonization in measuring techniques, and modelling of skid resistance of asphalt concrete pavement have been provided. Although several past studies have provided literature review on general topics of skid resistance, to the best of the author's knowledge, none of them have compressively covered the topic considering the status & requirements of developing nations. There has been significant development in speed with the improvement in computational facilities. In modern times, with the improvement in infrastructure quality in developing nations, permitted speeds have also drastically increased. To avoid skid-related accidents, it is important to develop good practices in maintaining sufficient skid resistance. The requirements and the availability of technology might be significantly different in developing nations. The suitability and limitations of various methods used for capturing the skid characteristics of the surface have been outlined. The harmonization in skid resistance measurement using laboratory and field-testing methods has been summarized. Correlation analysis of various in-situ and laboratory test data has been made to maintain a better harmony of measurement either in the field or in the laboratory. In the subsequent sections, progress in the modelling approach (analytical to numerical) has been discussed in brief. Computational capabilities of an analytical and numerical modelling approach for predicting pavement skid resistance characteristics have been reviewed. These models have been developed to consider complex attributes of tire pavement interactions like hydroplaning, temperature rise in the tire, mix morphology, tire inflation, and vehicle acceleration and deceleration for predicting skid resistance. These attributes of skid resistance have been discussed in detail and presented a basic overview of the model development process which is missing in past review studies. Few recent studies on skid resistance measurement and modelling to highlight the use of new technology and improvements over conventional techniques have been presented in the manuscript which has not been reviewed earlier. Critical factors affecting the skid resistance model like hydroplaning, tire-related parameters, temperature, and surface texture have been highlighted in this manuscript. Few key research directions have been suggested as the scope of future study to predict a more reliable skid resistance model.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: FE model; Numerical solutions; Skid resistance; Surface texture; Tire-pavement interaction; Finite element method; Forecasting; Laboratories; Morphology